Influence of the level of speed-strength preparedness on the agility of volleyball players 12-13 years old - Shevchenko, O.; Paievskyi, V.; Horchanyu, Y. (Slobozhanskyi herald of science and sport, 2018)
Purpose: determine the impact level of indicators of speed-strength preparedness for the agility of young volleyball players 12-13 years.